Modelling the time variable spectral energy distribution of the blazar CTA 102 from 2008 to 2022. Issue 2 (7th October 2022) - Sahakyan, N; Israyelyan, D; Harutyunyan, G; Gasparyan, S; Vardanyan, V; Khachatryan, M
ABSTRACT: We present long-term multiwavelength observations of blazar CTA 102 (z = 1.037). Detailed temporal and spectral analyses of γ-ray, X-ray, and UV/optical data observed by Fermi -LAT, Swift XRT, NuSTAR, and Swift -UVOT over a period of 14 yr, between 2008 August and 2022 March, were performed. We found strong variability of source emission in all the considered bands; especially in the γ-ray band it exhibited extreme outbursts when the flux crossed the level of 10 −5 photon cm −2 s −1 . Using the Bayesian Blocks algorithm, we split the adaptively binned γ-ray light curve into 347 intervals of quiescent and flaring episodes and for each period built corresponding multiwavelength spectral energy distributions (SEDs), using the available data. Among the considered SEDs, 117 high-quality (quasi) contemporaneous SEDs, which have sufficient multiwavelength data, were modelled using jetset framework within a one-zone leptonic synchrotron and inverse-Compton emission scenario assuming the emitting region is within the broad-line region and considering internal and external seed photons for the inverse-Compton upscattering. As a result of modelling, the characteristics of the relativistic electron distribution in the jet as well as jet properties are retrieved and their variation in time is investigated. The applied model can adequately explain the assembled SEDs and the modelling shows that the data in the bright flaring periods can be reproduced for high Doppler boosting and magnetic field. The obtained results are discussed in the context of particle cooling in the emitting region.